UPAYA GURU PAI DALAM MENINGKATKAN LITERASI MEMBACA PESERTA DIDIK MELALUI PEMBELAJARAN PAI (Studi Deskriptif di Kelas XI SMA Negeri 11 Bandung) - Ilham Nasrulloh, - (2021)
This research is motivated by facts that show the very low interest in reading students. Remembering reading is an important factor because by reading we can add insight and knowledge. Researchers consider the efforts of Islamic Education teachers in improving students 'reading literacy through Islamic Education learning can regrow students' asking for reading where we are faced with modern conditions. The purpose of this study in general was to describe the efforts of Islamic education teachers in improving students' reading literacy through Islamic education learning. This study uses a qualitative approach with descriptive methods. This research was conducted at SMA Negeri 11 Bandung which is located on Jalan Mohamad Toha No.178 Bandung. With the research subject of teachers and students. Data collection was carried out by interview, observation, and documentation, then analyzed through stages of reduction, display, to data verification. The research results (1) the literacy program used by Islamic Education teachers, namely: reading 7-15 at the beginning of the lesson, reading articles 1 week once, and reading books 2 weeks once. (2) the sources of reading literacy used by Islamic Education teachers include: textbooks, e-books, articles, free reading books. (3) the results of the measurements made by Islamic Education teachers to measure the level of student achievement from several tests carried out showed that students were able to understand the reading well. (4) the benefits after the implementation of the literacy program by Islamic Education teachers include: the perceived benefits of increasing insight, knowledge, sharpening reasoning, fostering a love for reading, and making students literate. Keywords : PAI Teacher, Literacy, Reading, Science.